Quantifying material loss from the bearing surfaces of retrieved hip replacements: Method validation. (February 2020) - Bergiers, Sean; Hothi, Harry; Richards, Robin; Dall'Ava, Lorenzo; Henckel, Johann; Hart, Alister
Abstract: Computational methods used to quantify wear in failed hip arthroplasties are often limited by human and sampling errors. An automated software solution has been developed to overcome these shortcomings. The overarching aim of the current study was to validate this method through a comparison with gravimetric measurements. Seventy-two different wear volumes were quantified to within a mean error of 0.14 mm 3 and 0.10 mm 3 of gravimetric results for simulated cup and head components, respectively. This approach had an improved accuracy, repeatability and reproducibility over a commonly used, commercially available software solution, which bears many of the common sources of error. Highlights: This article validates an automated method for quantifying wear in hip implants. Bearing surface wear volumes were quantified to a maximum mean error of 0.14 mm 3 . An automated solution provides improved accuracy compared to a commercial software. Potential impact for a million patients world-wide with metal-on-metal hips.